Design of Flood Control Hydrological Information Measurement and Forecast System in a Certain Area. Issue 6 (April 2020) - Li, Dacan; Gong, Yuanyuan; Li, Dezheng; Shen, Shufei; Wang, Lei
Abstract: In recent years, hydrological information in this area has played an important role in flood control and drought relief, and achieved good social, economic and ecological benefits, but there is still a certain gap with the latest requirements of the state in hydrological. With the rapid expansion of hydrological information collection stations and the rapid increase of station network density, considering the current needs of local hydrological information management, hydrological management departments and flood control and Drought Relief Command departments, this paper uses software engineering method to design a hydrological information measurement and reporting system. The system realizes centralized management of water information, real-time information query and analysis, dynamic monitoring and alarm, auxiliary decision-making, remote data collection and other hydrological business functions and provides decision support for leaders of all departments. It plays an important role in the success of flood control and drought relief work to minimize the loss of disasters and ensure the safety of people's lives and properties with the least human and material resources.